2019
DOI: 10.7759/cureus.4676
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pancreatitis Secondary to Use of Appetite Suppressant: Garcinia cambogia

Abstract: Due to the global epidemic of obesity, weight loss and appetite suppressant herbal products are quite popular. As these medications are not United States Food and Drug Administration-approved and are regulated as dietary supplements, little evidence exists regarding their safety. This case discusses an 82-year-old man with the past medical history of obesity who presented to the emergency department with abdominal pain in the epigastric region. His serum lipase was elevated, and an abdominal computed tomograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…144,145 A clinical investigation of a 82-year-old male, after the consumption of G. cambogia, revealed that the patient had fats deposited around the pancreas that was well-matched with acute pancreatitis. 146 Moreover, a report suggested that a 35-year-old female consumed G. cambogia and soon developed nausea, headache, dizziness and swelling of the eyes. 147 The safety of G. cambogia is controversial and not properly established.…”
Section: Resultsmentioning
confidence: 99%
“…144,145 A clinical investigation of a 82-year-old male, after the consumption of G. cambogia, revealed that the patient had fats deposited around the pancreas that was well-matched with acute pancreatitis. 146 Moreover, a report suggested that a 35-year-old female consumed G. cambogia and soon developed nausea, headache, dizziness and swelling of the eyes. 147 The safety of G. cambogia is controversial and not properly established.…”
Section: Resultsmentioning
confidence: 99%
“…These case reports include various dietary supplements containing a mixture of compounds: Hydroxycut™, Topine® 10 Kalo®11, Exilis (Garcinia cambogia, Garcinia sylvestre,L-carnintine and chrome), "Garcinia cambogia pure", multi ingredient protein supplement with Garcinia cambogia (70%), SUPER ANANAS SLIM™: Garcinia cambogia (60%), Ananas comosus and Ilex paraguariensis, OBLESS™: Garcinia cambogia (72 mg of HCA) and other components: 1 capsule/day AndMagistral preparation of different herbsextracts), THERMO GIALLO™: Garcinia cambogia (200 mg HCA) and 2 capsules of chromium. Acute pancreatitis (Grigos et al, 2016;Bystrak et al, 2017;Iqbal et al, 2019) Case reports Three cases have been reported of acute pancreatitis secondary to the use of Garcinia gummi-gutta (L.) N.Robson, as dietary supplement (Grigos et al, 2016;Bystrak et al, 2017;Iqbal et al, 2019) Serotonine syndrome, hypomania (Roy et al, 2004) (Narasimha et al, 2013;Lopez et al, 2014;Beecheno et al, 2016;Hendrickson et al, 2016;Wong et al, 2016;Cotovio and Oliveira-Maia, 2017;Nguyen et al, 2019;Nam et al, 2022) Rat studies…”
Section: Hibiscus Sanguineus Griffmentioning
confidence: 99%
“…He denied any alcohol use and reported no recent changes in his medications, as well as the intake of Garcinia cambogia recently as an appetite suppressant. He was treated with bowel rest and intravenous fluid hydration, providing a significant improvement in his symptoms [ 62 ].…”
Section: Negative Effects On Healthmentioning
confidence: 99%